2023
DOI: 10.1002/cbdv.202200730
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 Protects against Cardiac Remodeling in Heart Failure via SIRT1/PINK1/Parkin‐Mediated Mitophagy

Abstract: Adverse cardiac remodeling may lead to the development and progression of heart failure, which is lack of effective clinical treatment. Ginsenoside Rg1 (GRg1), a primary ingredient of Panax ginseng, protects against diverse cardiovascular disease, but its effects on cardiac remodeling remain unclear. Thus, we investigated the protective effect and mechanism of GRg1 on cardiac remodeling after myocardial infarction. GRg1 significantly ameliorated cardiac remodeling in mice with left anterior descending coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Similar effects were seen with ginsenoside Rg1, which reduced hypertrophy, oxidative stress and proinflammatory signalling in streptozotocin induced diabetic hearts, while upregulating AMPK and PGC‐1α 161 . In post‐infarction heart failure, ginsenoside Rg1 alleviated left ventricular dilatation and fibrosis and promoted mitophagy, and the enhancement of mitophagy by ginsenoside Rg1 in hydrogen‐peroxide treated cardiomyocytes was prevented by SIRT1 inhibition 162 . In isoproterenol‐induced heart failure, ginsenosides Rb1 and Re ameliorated cardiac injury and fibrosis, while upregulating PPARα and improving mitochondrial function and fatty acid oxidation 163,164 …”
Section: Qiliqiangxin In Experimental Models Of Prolonged Measured Ca...mentioning
confidence: 55%
See 1 more Smart Citation
“…Similar effects were seen with ginsenoside Rg1, which reduced hypertrophy, oxidative stress and proinflammatory signalling in streptozotocin induced diabetic hearts, while upregulating AMPK and PGC‐1α 161 . In post‐infarction heart failure, ginsenoside Rg1 alleviated left ventricular dilatation and fibrosis and promoted mitophagy, and the enhancement of mitophagy by ginsenoside Rg1 in hydrogen‐peroxide treated cardiomyocytes was prevented by SIRT1 inhibition 162 . In isoproterenol‐induced heart failure, ginsenosides Rb1 and Re ameliorated cardiac injury and fibrosis, while upregulating PPARα and improving mitochondrial function and fatty acid oxidation 163,164 …”
Section: Qiliqiangxin In Experimental Models Of Prolonged Measured Ca...mentioning
confidence: 55%
“…161 In post-infarction heart failure, ginsenoside Rg1 alleviated left ventricular dilatation and fibrosis and promoted mitophagy, and the enhancement of mitophagy by ginsenoside Rg1 in hydrogen-peroxide treated cardiomyocytes was prevented by SIRT1 inhibition. 162 In isoproterenol-induced heart failure, ginsenosides Rb1 and Re ameliorated cardiac injury and fibrosis, while upregulating PPARα and improving mitochondrial function and fatty acid oxidation. 163,164 Little is known about the effect of astragaloside IV, tanshione IIA and ginsenosides on PPARγ in the heart.…”
Section: Effect Of Qiliqiangxin Constituents On Sirt1-ampk-pgc-1𝛂-ppa...mentioning
confidence: 99%
“…Research showed that Ginsenoside Rg1 signi cantly improved cardiac remodelling in left anterior descending coronary artery ligated mice, as evidenced by a reduction in cardiac brosis accompanied by an improvement in cardiac function. The mechanism was that ginsenoside Rg1 signi cantly increased mitochondrial formation, improved cardiac mitochondrial damage and enhanced SIRT1/PINK1/Parkin-mediated mitophagy during cardiac remodelling [13] However, the effects of the other two active components on mitophagy have not been investigated, and therefore further experimental validation of the above monomers is required to reveal their effects and mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that the activation of the PINK1/Parkin pathway can prevent mitochondrial damage and cardiomyocyte apoptosis by increasing the level of mitochondrial autophagy ( 157 ), improve cardiac contractile function ( 158 ), and reduce heart failure( 159 ). There are studies ( 160 , 161 ) reporting that Nuanxinkang can prevent the development of myocardial infarction-induced chronic heart failure by promoting PINK1/Parkin-mediated mitophagy and ginsenoside Rg1 can protect against cardiac remodeling in heart failure via SIRT1/PINK1/Parkin-mediated mitophagy.…”
Section: The Mechanism Of Tcm In Treating Refractory Heart Failurementioning
confidence: 99%